2022
DOI: 10.2903/j.efsa.2022.7144
|View full text |Cite
|
Sign up to set email alerts
|

Pest categorisation of Zaprionus indianus

Abstract: The EFSA Panel on Plant Health performed a pest categorisation of Zaprionus indianus (Diptera: Drosophilidae), the African fig fly for the territory of the EU. This species successfully colonised the Indian subcontinent more than four decades ago, and more recently South and North America. Within the EU, the pest occurs in Cyprus, Malta, Portugal (Madeira) and Spain (Canary Islands and Andalusia). Z. indianus is not listed in Annex II of Commission Implementing Regulation (EU) 2019/ 2072. The larvae of this fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Yet, the ability of Z. indianus to oviposit and generate offspring in healthy strawberry fruit was clearly facilitated by injuries caused by D. suzukii or by mechanical injuries (42). Although no specific report of damage by Z. indianus in the EU has been reported so far, considering the damage caused to figs in South America, Z. indianus establishment and spread was considered as a threat with possible large economic consequences in Europe (43). Consequently, in 2022, Z. indianus was considered by European Food Safety Authority as a potential Union quarantine pest (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the ability of Z. indianus to oviposit and generate offspring in healthy strawberry fruit was clearly facilitated by injuries caused by D. suzukii or by mechanical injuries (42). Although no specific report of damage by Z. indianus in the EU has been reported so far, considering the damage caused to figs in South America, Z. indianus establishment and spread was considered as a threat with possible large economic consequences in Europe (43). Consequently, in 2022, Z. indianus was considered by European Food Safety Authority as a potential Union quarantine pest (43).…”
Section: Resultsmentioning
confidence: 99%
“…Although no specific report of damage by Z. indianus in the EU has been reported so far, considering the damage caused to figs in South America, Z. indianus establishment and spread was considered as a threat with possible large economic consequences in Europe (43). Consequently, in 2022, Z. indianus was considered by European Food Safety Authority as a potential Union quarantine pest (43). Our results suggest that a particular attention should be paid also on Z. tuberculatus .…”
Section: Resultsmentioning
confidence: 99%
“…Since the invasion, the species has rapidly spread throughout the country (Commar et al., 2012; Rios et al., 2022) and has become a significant pest in fig crops, causing major economic impacts (Commar et al., 2012; Vieira et al., 2019; Vilela & Goñi, 2000). Other studies have shown that Z. indianus is detrimental to the cultivation of tomato, guava, mango, cherry, and blueberry (Bragard et al., 2022; Khaldi et al., 2021).…”
Section: Introductionmentioning
confidence: 97%
“…. Other studies have shown that Z. indianus is detrimental to the cultivation of tomato, guava, mango, cherry, and blueberry (Bragard et al, 2022;Khaldi et al, 2021).…”
mentioning
confidence: 93%
“…Indeed, females of Z . indianus produce around 70 eggs, can pause ovarian development during cold periods without loss of fertility [ 2 , 13 ], and complete 12 to 16 generations per year. Dissimilarly, Drosophila suzukii females are highly fertile and lay more than 200 eggs during their lifetime [ 14 ].…”
Section: Introductionmentioning
confidence: 99%